Composition and acaricidal activity of the essential oil of Lychnophora ericoides Mart. to Tetranychus urticae Koch (Acari: Tetranychidae). - Baldan, E.L.L.; Dal Pogetto, M.H.F.A.; Pavarini, D.P.; Lopes, N.P.; Lopes, J.L.C. (My University, 2010)
The essential oil of the leaves and branches obtained by hydrodistillation of Lychnophora ericoides, collected in the Reserve of Furnas - MG, Brazil, was analyzed by CG/EM (Shimadzu QP2010). The major parts of the volatile components identified in the essential oil of leaves were monoterpenes (44.02%) and the sesquiterpene [alpha]-bisabolol (2.05%). The major acaricidal activity of the essential oil from L. ericoides was observed at 48 (14.55 [mu]L/L of air) and 72 h (8.01 [mu]L/L of air) of exposition. The oviposition of T. urticae oviposition was influenced by the essential oil, but the eclosion of eggs was not affected.